Žuvies užtepėlių gamybos tyrimas UAB „Maistas“ - Filipčiukova, Ana (Institutional Repository of Klaipeda State College, 2021)
The product under development is spreads made of the Acipenser Baerii fish, which is highly nutritious and has a high protein nutritional value. The thesis analyses the amino acids in Acipenser Baerii, which are essential for the human body. Not only the fillets but also other parts of the fish, such as skin and cartilage, are used. Calculations of the nutritional value have been carried out, which show that the spread is high in protein and low in calories. Calculations of the economic indicators have been carried out, which have shown that the product will be profitable.